The Role of Parents in Guiding Children to Learn Online During the Covid 19 Pandemic - Wahib, Ahmad (STAI MA'ARIF MAGETAN, INDONESIA, 2021)
The covid 19 pandemic has led to the issuance of rules for studying from home for school children and working from home for teachers. The current situation demands maximum involvementof parents and restore the nature of children’s education in the family. The role of parents in guilding children is very much, parents not only function as the firdt and foremost place for children’s education in shaping character but now have an additional role as second teachers for children in learning at home. Accompanying children when studying is something that is very important for children, namely to build closeness between parents and children, especially when at home during this pandemic. One of its roles is to familiarize children to always study hard in the online learning process. Some ways that can be done by parents are supervising, paying attention to children in doing school assignments, providing anthuasasm and motivation for children in the learning process.